Clinicomicrobiological spectrum of abnormal discharge from vagina in women in costal Andhra Pradesh - Singamsetty, Jyothi; Sravani, G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: When there is change in colour, consistency, order and volume of discharge then it is called abnormal vaginal discharge and associated with vulvar pruritus, dyspareunia, dysuria and lower abdominal pain. There is variability in organism isolated and treatment used. Methods: Sexually active women in reproductive age group with complain of abnormal vaginal discharge were included in this study based in following inclusion and exclusion criteria. . A detailed history of patient was taken regarding nature of discharge, colour, smell along with dysuria, dyspareunia, itching of vulva and lower abdominal pain. Results: Out of 160 patients 88 patients have bacterial vaginosis. Trichomonas vaginitis was present in 7.5% patients. Candidiasis was present in 6.25% patients. Some patients were having more than one infection like Bacterial vaginosis and Trichomonas vaginitis was coexisting in 13.75%, Bacterial vaginosis + Candidiasis were present in 8.75% patients. Mixed infection was present in 8.75%. Conclusions: From present study we can conclude that vaginal discharge is more common in married women in young age. Patients commonly presented with curdy white discharge, pruritus vulva and lower abdominal pain. Erythema and excoriation in vulva were common presentation, followed by erythema of vagina. Nature of discharge was mucopurulent in most patients. Bacterial vaginosis was most common followed by Trichomonas vaginitis.